Morphometric analysis of anatomical reference points in hip surgery: A study on cadaveric and radiographic images - Kabakcı, Ayşe Gül; Biçer, Ömer Sunkar; Bozkır, Memduha Gülhal (The European Research Journal, 2025)
Objectives: This study aims to evaluate the accuracy of morphometric measurements obtained from cadavers and anteroposterior (AP) pelvic radiographs. Methods: A total of 15 cadavers from the anatomical collection of Cukurova University and 217 AP pelvic radiographs from individuals aged 65-80 years with no orthopedic conditions were analyzed. Morphometric measurements were taken from cadavers using Kirschner wires placed at anatomical reference points: the spina iliaca anterior superior (SIAS), the highest point of the crista iliaca (CI), and the trochanter major (TM). Distances were measured with a non-elastic tape, and angular measurements were conducted using ImageJ software. These were compared with radiographic data analyzed via the PACS system. Statistical analysis was performed using SPSS 20 with One-Way ANOVA to assess group differences. Results: The mean age was 70.98±4.70 years for radiograph individuals and 80.36±5.13 years for cadavers. Significant differences were found between cadaveric, dissected cadaver, and radiological measurements. The SIAS-TM distance was longest in cadavers (113.82±7.46 mm) and shortest in radiographs (92.73±14.36 mm). The CI-TM distance was greatest in radiographs (147.81±12.02 mm), while the SIAS-CI distance was longest in cadavers (78.95±6.48 mm). Differences in SIAS-TM (P